Diffraction by an Arbitrary-Angled Dielectric Wedge: Part Ii-Correction to Physical Optics Solution - Kim, S.-Y.; Ra, J.-W.; Shin, S.-Y. (1991)
In Part I of these two companion papers, the physical optics solution for the diffraction by an arbitrary-angled dielectric wedge was derived from the formulation of the dual integral equation. In this paper, the error of the physical optics solution for the E-polarized planewave incidence is corrected by calculating the nonuniform current distributed along the dielectric interfaces. Two kinds of series expansions to the nonuniform current are employed here. One is an asymptotic expansion as the multipole line source located at the edge of the dielectric wedge since the correction field seems to be a cylindrical wave emanating from the edge in farfield region. The other is arbitrary electric and magnetic surface currents expanded by infinite series of the Bessel functions, i.e., the Neumann's expansion, of which fractional order is chosen to satisfy the edge condition near the edge of the dielectric wedge in the static limit. Both of the two different expansion coefficients for wedge angle 45°, relative dielectric constant 2, 10, and 100, and the E-polarized incident angle 150° are evaluated by solving the dual series equation numerically after finite truncation. The farfield patterns are calculated and the validity of the two different expansions is also discussed. ？ 1991 IEEE